Asset Prices and Leverage in a Model of Persistent Stagnation - Matthias Schlegl; Gerhard Illing; Yoshiyasu Ono (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We use a stylized MIU-model with a housing sector and financial frictions to study the interactions between debt, liquidity and asset prices under persistent stagnation. Stagnation can occur in equilibrium when households have insatiable liquidity preferences. We show that financially more advanced economies are more likely to enter into stagnation and that stagnation is more severe the higher private sector debt. Moreover, credit booms can temporarily mask the transition into stagnation.
Keywords: 330